Increasing Chinese Influence in Sri Lanka : Impact of Indian Geo Strategic Interest - Ganeshalingam, K.T.; Moorthy, P. (UGC Centre for Southern Asia Studies, Pondicherry University, 2013)
Over the last two decades in the diplomatic ties between China and Sri Lanka, China has emerged as a vital force in Sri Lanka's military, economic, politics and social development. In the contemporary circumstances the perceivable reason for Sri Lanka to choose China as a friendly country is largely due to the approach of America and its western allies. In the context of Chain's huge and generous military and economic aid towards Sri Lanka, though the aim of Sri Lanka has become development oriented, yet, India being its closest neighbor views these moves with suspicion and apprehension. The India - Sri Lanka ties have become weak and China - Sri Lanka ties have become strong and important. Sri Lanka since it gained independence was part of the geopolitical interest of India. In order to free it from Sri Lanka for a long time, she had established close relationship with the western countries. However when western countries made policy shifts and placed increased conditions on the economic aid given to Sri Lanka, gradually Sri Lanka began to distance itself from the west. This coincided with China's prosperity and its approach. China by way of helping Sri Lanka with military hardware and economic assistance for its geo - political and geo - strategic interest in the Indian Ocean region. The Crown of the recent Chinese support to Sri Lanka was the agreement on Hambantota harbour, near one of the world's biggest shipping lanes. However, considering the strategic contest between India and China in the Indian Ocean region, any India - Sri Lanka deal does not seem to be match with the deal to fund the Hambantota harbour project by The primary objective of the Hambantota project is to sow the same times different aspects of development such as shipping, trans - shipment, shipbuilding, and catering to increase exports and imports, for which the Port of Colombo does not have enough space and facilities.